Counseling Counseling on Preventing Stunting Starting from the Family by Improving Nutrition and Sanitation and Complete Immunization in Lanto Jaya Village, Poso Regency: Penyuluhan Cegah Stunting Mulai dari Keluarga dengan Perbaiki Gizi dan Sanitasi serta Lengkapi Imunisasi di Desa Lanto Jaya Kabupaten Poso - Lilis Candra Yanti; H. Hatijar; Sri Hardiyanti (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
This service aims to provide education to the community about how to prevent stunting starting from the family itself, namely by improving daily food nutrition, improving environmental sanitation and completing child immunization. Stunting is one of the health problems in Indonesia which is still quite high, one of which is the Poso Regency area which also contributes to the incidence of stunting. Stunting is classified as a chronic nutritional problem caused by many factors including economic conditions, maternal nutrition during pregnancy, infant pain, lack of nutritional intake as a toddler. This service has been carried out in Lanto Jaya Village, Poso Pesisir, Poso Regency with counseling methods as well as discussions or questions and answers with participants. The results of the counseling show that the community still does not understand the problem of stunting and the causes of stunting and the future impact on their children if they experience stunting. With this counseling, the community understands better and is very helpful for Puskesmas cadres in providing understanding or knowledge to the community. Abstrak Pengabdian ini bertujuan untuk memberikan penyuluhan kepada masyarakat tentang bagaimana pencegahan stunting yang dimulai dari keluarga sendiri yaitu dengan memperbaiki gizi makanan sehari-hari, memperbaiki sanitasi lingkungan serta melengkapi imunisasi anak. Stunting merupakan salah satu masalah kesehatan di Indonesia yang masih cukup tinggi, salah satunya daerah Kabupaten Poso juga penyumbang angka kejadian stunting. Stunting tergolong masalah gizi kronik yang disebabkan banyak faktor diantaranya kondisi ekonomi, gizi ibu saat hamil, kesakitan pada bayi, kurang asupan gizi saat balita. Pengabdian ini telah di lakukan di Desa Lanto Jaya, Poso Pesisir Kabupaten Poso dengan metode penyuluhan serta diskusi atau tanya jawab dengan peserta. Hasil penyuluhan menunjukkan bahwa masyarakat masih kurang paham terkait dengan masalah stunting dan penyebab stunting dan dampak kedepan dengan anak mereka jika mengalami stunting. Dengan adanya penyuluhan ini masyarakat lebih paham serta sangat membantu kader-kader Puskesmas memberikan pemahaman atau pengetahuan kepada masyarakat.